3D visualisation of wearable inertial/magnetic sensors - Wada, T.; Mizutani, M.; Lee, J.; Rowlands, D.; James, D. (Proceedings, 2018)
Inertial and inertial-magnetic sensors are miniaturised and lightweight which allows the technology to be used to assess human movements in sports. These sensors can produce up to nine channels of time series data which can often be difficult to read and interpret. This paper describes the development of a 3D visualisation tool for inertial/magnetic sensors. A sensor fusion technique known as an attitude heading reference system (AHRS) is used to calculate 3D orientation of the sensor. With AHRS data from a gyroscope and magnetometer can be expressed in animation as orientation of the sensor. However acceleration does not appear in the animation. Therefore the function to express the magnitude and direction of the acceleration using a shake of the sensor animation is added to the tool. It was confirmed that the tool produce an animation which clearly portrayed athlete posture and accelerations synchronised with the gait cycle.